2013
DOI: 10.2301/neurosonology.25.91
|View full text |Cite
|
Sign up to set email alerts
|

Optimal length of intramuscular injection needle and drug absorption by ultrasound evaluation

Abstract: The administration of an intramuscular injection (IMI) is a basic nursing skill, primarily involving the gluteus and deltoid muscles. Nurses must determine the appropriate needle type, gauge, and depth of insertion for giving an IMI while avoiding injury to blood vessels and nerves. The primary purposes of this study were to determine the appropriate depth of injection for administering risperidone long-acting injectable (RLAI) and to evaluate the injected drug absorption using B-mode ultrasonography. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It is important to note, however, that the procedure for data collection was used in four other successful investigations by Tanioka, Yasuhara, and Sakamaki et al [19]- [21] [32]. This procedure provided credible data on diffusion location, rates, and absorption using RLAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, however, that the procedure for data collection was used in four other successful investigations by Tanioka, Yasuhara, and Sakamaki et al [19]- [21] [32]. This procedure provided credible data on diffusion location, rates, and absorption using RLAI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study [18] reports injection needle lengths for optimal IM injection for adult subjects. Previous research using ultrasonographic data is used to detect insertion sites [19], depth of needle insertion into specific muscles [20], and visualization of medication dispersions [21].…”
Section: Introductionmentioning
confidence: 99%
“…This was evidenced by using an ultrasonic diagnostic apparatus 14) . Also, it was observed that both RLAI and ALAI were depicted as having high echogenicity with acoustic shadowing and high echogenic mass in the gluteus medius 15) .…”
Section: Evaluations Of Muscle Echogenicities In Patients Treated Witmentioning
confidence: 99%
“…In previous studies using ultrasonography, the "distance from the epidermis to the under-fascia" and "distance from the epidermis to the iliac bone" of the buttocks at the dorsogluteal and ventrogluteal sites in healthy Japanese volunteer subjects 8) and patients with schizophrenia were measured 9,10) in order to evaluate the optimal IM injection needle length 11) and the optimal gluteal muscular injection needle should be 40-50mm in length. The IM administrated LAIs showed high-echogenicity masses with acoustic shadowing 12,13) .…”
mentioning
confidence: 96%